Depression and quality of life of university professors in Southern Brazil - Machado, Thayla Rauch (2021)
Depression often causes disability and is associated with decreased productivity and work performance, limiting the social contribution of the bearer of its symptoms and causing a negative impact on the individual’s life. Professors are a category of professionals exposed to psychosocial risks, to stress-triggering factors inherent to the academic and school organization, and to situations where the professional’s individual expectations and the reality of daily work are unbalanced. Hence, this cross-sectional and quantitative study investigates the association between depression and quality of life of university professors, carried out with professors from a federal university. Quality of life was analyzed by a questionnaire, sent by e-mail to the participants, named The Medical Outcomes Study 36-item Short Form Health Survey (SF-36), and depression by self-reported medical diagnosis. Other variables were analyzed by a semi-structured questionnaire. Statistical analysis was performed using the variance test. Of the 680 professors identified, 270 (40%) were included in the sample. Prevalence of depression was 6.3% (95% CI 3.4 to 9.2). Depression was associated with lower quality of life scores in the domains: functional capacity, pain, general health, vitality, social aspects, and mental health. The other domains did not reach statistical significance. Depression negatively influenced the quality of life of the university professors studied.